PsycEXTRA Dataset 2002
DOI: 10.1037/e446332006-001
|View full text |Cite
|
Sign up to set email alerts
|

Actual and perceived cognitive performance during acute altitude exposure

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing, the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…performance parameters. For example, increase in speed of card sorting task completion at 8000 ft (2438 m) ( 50 ); better logical reasoning performance at 8000 ft compared with 5000, 10,000, and 12,000 ft (1524, 3048, and 3658 m) ( 69 ); better cognitive performance and memory scores at 10,000 ft (3048 m) compared to ground and 14,000 ft (4267 m) ( 86 ); and an improved auditory reaction time when HbS o 2 dropped to 90% ( 90 ). Several studies did not fi nd any effects of moderate altitude or equivalent gas mixture on cognitive function at 10,000 ft ( 7 ) They concluded that selected cognitive and affective frontal lobe functions were preserved despite signifi cant HbS o 2 desaturation and a drop in diastolic blood pressure.…”
Section: Cognitive and Psychomotormentioning
confidence: 99%
“…performance parameters. For example, increase in speed of card sorting task completion at 8000 ft (2438 m) ( 50 ); better logical reasoning performance at 8000 ft compared with 5000, 10,000, and 12,000 ft (1524, 3048, and 3658 m) ( 69 ); better cognitive performance and memory scores at 10,000 ft (3048 m) compared to ground and 14,000 ft (4267 m) ( 86 ); and an improved auditory reaction time when HbS o 2 dropped to 90% ( 90 ). Several studies did not fi nd any effects of moderate altitude or equivalent gas mixture on cognitive function at 10,000 ft ( 7 ) They concluded that selected cognitive and affective frontal lobe functions were preserved despite signifi cant HbS o 2 desaturation and a drop in diastolic blood pressure.…”
Section: Cognitive and Psychomotormentioning
confidence: 99%
“…Conscious processes tend to be resource consuming and effortful (Bargh, 1994), and therefore reduced air resource might reduce conscious processes. Increased oxygen intake has been found to benefit (Moss, Scholey, & Wesnes, 1998), and decreased intake to harm (Terry, 2001), conscious processes. Oxygen intake is reduced during sleep, and conscious…”
Section: Introductionmentioning
confidence: 99%
“…Performance generally was impaired at the lowest oxygen levels. Participants performed more poorly at 10,000 than 14,000 feet on a divided attention task (Terry, 2001). Volunteers exhibited impaired performance on cognitive tasks at simulated higher altitudes (Crowley et al, 1992;Gerard, 2000 (Moss et al, 1998).…”
Section: Introductionmentioning
confidence: 99%